Effect of temperature variation on Aman and Boro rice production of Barisal division in Bangladesh - Karmokar, J; Billah, MM; Haque, MA (Progressive Agriculture, 2019)
A study was undertaken to study the impact of seasonal temperature variation on Aman and Boro rice production in Barisal division of Bangladesh. The study revealed that the relationship between changing patterns of seasonal mean temperature and yield of rice, which illustrates the average mean temperature for the correlation of time series data from 1958-2008. The regression model is used to analyze the different temperature trends, and to identify the possible factors and causes of these differences. The value of t-statistic for slope and p-value for different regression equations are estimated. Results show that the average maximum temperature is risk increasing for Boro, while it is risk decreasing for Aman for the period of 2006-2008. Besides, minimum temperature is risk increasing for Boro during 1994-2008 but it is risk decreasing for Aman except the year 1998. We observed that the summer temperature has been rising up during the period 1958-1974 and fallen down for 1992-2008. The average annual temperature changes from 0.5˚C to 1˚C over the period from 2005 to 2008 which impact on Aman and Boro rice yield. Therefore, the predictive approach provides an outline for future risk of the minimum temperature that has the impact on rice yield than maximum temperature, which can be used for rice production for its better management strategies. Progressive Agriculture 30 (1): 95-103, 2019